LOCAL GOVERNMENT AND SUSTAINABLE NATIONAL DEVELOPMENT IN NIGERIA - Idike, Adeline Nnenna (European Scientific Journal, ESJ, 2014)
It is argued in this study that despite the claims by state officials to the contrary, the pace of national development in Nigeria remains abysmally in a negative position. In the Nigerian state therefore, it has largely remained a scenario of affluence and affliction. The local government areas have also largely remained underdeveloped. It is further posited in this contribution that the issue of sustainable national development in Nigeria is immensely intertwined with developments in the local government system. Hence, it is concluded in this study that one of the best ways of going about the overall development of the Nigerian state is to concentrate on the development of its local government segments.